ASISTEM INFORMASI PERPUSTAKAAN SEKOLAH SMPN 8 KOTA SERANG - Rahadian Arief; Asep Sapaatullah; Muhammad Arya Febriansyah; Yasin Efendi; Syifa Faridah; Agung Firmansyah (Jurnal Ilmiah Sistem Informasi, 2022)
With the development of information technology today, where the activities of daily life will be computer-based. So in a computer agency is a material need in creating and obtaining information. Of the various kinds of information technology, currently in demand by the public is about technology related to computers. The purpose of this study is to analyze the library information system that is currently running at SMP N 8 Serang City to be better, to design a new information system at the library at SMP N 8 Serang City.The development of information systems requires proper analysis to be able to map out the problems and weaknesses of the old system in advance. There are several methods that can be used to analyze the system, one of which is the PIECES method (performance, information, economic, control, efficiency, and service). Input process until the data output process will be more accurate, and can reduce errors resulting from the system that is running at SMPN 8 Serang City Facilitate the making of reports that will be made by the user who will be reported to the head of the library, by building tables in the database. With this library application program, it is hoped that it can help officers in recording book loans and replace the old system